ASSA13-10-5 No Association Between PON1 Gene Single Nucleotide Polymorphisms and Clopidogrel Resistance in Chinese Han Population. (29th April 2013) - Tengfei, Liu; Xiaolin, Zhang; Wenzhi, Cai; Chenghui, Yan; Jian, Zhang; Ying, Sun; Yaling, Han
Abstract : Background: Clopidogrel requires bioactivation in vivo to convert the pro-drug into its active metabolite to show its antiplatelet effects. The variability in the clinical response to clopidogrel treatment has been attributed to genetic factors, but the specific genes and mechanisms underlying clopidogrel bioactivation remain unclear. Recent studies report that Paraoxonase-1 (PON1) as a key enzyme play vital part in clopidogrel bioactivation. Objective: The aim of our study was to assess whether PON1 gene polymorphisms are correlation with clopidogrel resistance (CR) in patients receiving clopidogrel after percutaneous coronary intervention (PCI). Methods: A total of 850 patients undergoing PCI were enrolled in this study, according to clopidogrel response which was assessed by post-treatment 20 μmol/L ADP -induced platelet aggregation ratio (PRA), RPA (RPA ≥ 70%) was defined as clopidogrel resistance (CR). We genotyped five SNPs of PON1 gene, the coding polymorphisms Q192R (rs662) and L55M (rs854560), the promoter polymorphisms –108C/T (rs705379), –162A/G (rs705381) and –909G/C (rs854572) variants by using polymerase chain reaction (PCR). In addition, activity level of PON1 towards phenylacetate was measured by spectro- photometrically at 270 nm. The SPSS 21.0 software was used to analyse all the included data. Results: The genotype frequencies of all studied SNPs were well to the Hardy-Weinberg equilibrium in both CR group and NCR group. Between the two groups, the five SNPs have the similar genotype and allele frequency (Q192R, P = 0.325 and 0.421; L55M, 0.806 and 0.499; rs705379, P = 0.426 and 0.263; rs705381, P = 0.513 and 0.484; rs854572, P = 0.482 and 0.798 respectively). The serum PON1 activity was lower in CR as compared to the NCR group, but not statistically significant ( P = 0.554). In the two groups, we did not observed any significant difference in PON1 gene polymorphisms and PON1 activity. Conclusions: This study demonstrates that neither PON1 gene polymorphisms nor PON1 activity are associated with CR in patients receiving clopidogrel after PCI.